IDENTIFIKASI HAMA DAN PENYAKIT Shorea Leprosula Miq DI TAMAN NASIONAL KUTAI RESORT SANGKIMA KABUPATEN KUTAI TIMUR PROVINSI KALIMANTAN TIMUR - Hariyanto Triwibowo; Jumani Jumani; Heni Emawati (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Pest and Disease Identification Shorea leprosula Miq in Kutai National Park Resort Sangkima East Kutai regency of East Kalimantan Province. The purpose of this study were: (1) To determine the frequency of pest and disease types meranti Shorea leprosula Miq. (2) To determine the intensity of pests and defect types meranti Shorea leprosula Miq. (3) To determine whether or not the prevention and control of pests and plant diseases meranti types Shorea leprosula Miq. This research was conducted in the Kutai National Park Resort Sangkima East Kutai in East Kalimantan Province. This study was conducted for two months effective the month of August 2012 until September 2012.The results of the research area of 1 ha with observations census found 11 Shorea leprosula Miq trees, with one tree physically healthy, 8 mild stricken trees, one tree is being attacked, and 1 heavy stricken trees. Arise and the presence of pests and plant diseases are often referred to as crop pests on crops and forests natural forests are mostly human intervention. From the calculation of the frequency of attacks on research plots by 91%, which means that almost all types of Shorea leprosula Miq indicated no pests and diseases while 9% were healthy. From the calculation of the intensity of pests and diseases of plants Shorea leprosula Miq, including the intensity of the attack was broken by 29.5%. Based on the identification of some pests and fungal diseases like cancer, stem, leaves and termite holes. The research concluded that the frequency of pest and disease Shorea leprosula Miq by 91%, the intensity of pests and diseases of the damaged condition of the stand, including 29.5% with the intensity of the attacks, control of pests and plant diseases do not need to be done because the condition only affected stands were . Recommended based on observation of pests and diseases types Shorea leprosula Miq need for monitoring human activities that can lead to new pests and diseases in forests Resort Sangkima which can reduce the quality and growth of the forest it self.